The hydrochemical response of small and shallow floodplain water bodies to temporary surface water connections with the main river. (29th December 2014) - Weigelhofer, Gabriele; Preiner, Stefan; Funk, Andrea; Bondar‐Kunze, Elisabeth; Hein, Thomas
Summary We investigated the effects of temporary surface water connections with the main river on the water chemistry of large and small waterbodies in a Danube floodplain by comparing hydrochemical data before, during and after water exchange with the Danube during two large floods in 2009 and 2013. In addition, we studied the effects of an increased frequency of flood pulses on the water chemistry of the floodplain via long‐term monitoring data. We used conservative (i.e. biologically non‐reactive) parameters (alkalinity, Ca, Cl, K, Mg, Na, SO4, conductivity) to identify hydrochemical changes due to the mixing with river water. Changes in non‐conservative parameters (PO4‐P, NO3‐N, NO2‐N, NH4‐N, total phosphorus, dissolved organic carbon, dissolved oxygen, chlorophyll‐a), which deviated from pure mixing effects, were ascribed to alterations of biogeochemical processes induced by the imported river water. In large floodplain waterbodies, both conservative and non‐conservative parameters changed towards Danube water concentrations during the connection with the main river and returned to pre‐connection levels after the water exchange ended. Only chlorophyll‐a concentrations were almost twice as high in the post‐connection phase than before the connection. In small floodplain waterbodies, conservative and non‐conservative parameters showed similar changes during the connection with the main river. However, the concentrations of PO4‐P, total phosphorus and chlorophyll‐a did not return to pre‐connection levels, but increased further in the post‐connection phase, exceeding even Danube water concentrations. We attribute these changes to phosphorus releases from the sediments and enhanced primary and bacterial production induced by the river water. In years with an increased flooding frequency, both conservative and non‐conservative parameters approached Danube water concentrations in large floodplain waterbodies due to the increased surface water exchange. In small floodplain waterbodies, conservative parameters remained unaffected by the increased connection with the river, while nitrate, ammonium, phosphate, total phosphorus and chlorophyll‐a concentrations were considerably higher in wet years than in dry years. We conclude that the temporary input of oxygen‐ and nutrient‐rich river water to small, mainly isolated backwaters can induce changes in benthic biogeochemical processes, which may provoke an internal eutrophication of these waterbodies.